Studies on chevron crickets: Contribution to the knowledge of Lutosinae/ini taxa (Orthoptera: Anostostomatidae) - Cadena-Castañeda, Oscar J.; García, Alexander García; Castellanos, Maria Del Pilar; Sarmiento, Juan Pablo Prias; Tavares, Gustavo Costa (Zootaxa, 2022)
In this contribution to the study of chevron crickets, we focus on several taxa of the subfamily/tribe Lutosinae/ini. Historical background was made on the classification of this group. Lutosa is redescribed, defining the generic and specific limits, thus providing a key for identifying the species based on males and another based on females. In addition, two new species are described: Lutosa morsellii n. sp. and Lutosa quaresmai n. sp.; L. marginalis, L. cubaensis and L. goeldiana were redescribed, and L. surda n. syn., was synonymized under L. paranaensis. Other species previously allocated in Lutosa are relocated as follows: Lutosa obliqua and L. azteca are again synonymized under Licodia pallipes; Lutosa inermis is moved back to Dolichochaeta (D. inermis comb. rev.). The genus Neolutosa is studied, grouping three species N. emarginata (with new specimens that rule out its presence in Central America), N. aculeata (with additional specimens, erroneously identified in the past as L. brasiliensis) and N. horribilis n. comb. (this species is transferred from Lutosa). A key to species is also provided. Records for Apotetamenus clipeatus are reported for the Brazilian Amazon and the states of Mato Grosso and São Paulo (Brazil). Finally, the classification of the family Anostostomatidae and the subfamily / tribe Lutosinae/nini is discussed.